(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The tragedy “Mirzo Ulug’bek” is dedicated to the restoration of historical truth in vivid artistic form, showcasing the life and work of the just king and great astronomer, Ulug’bek, with all its complexities, contradictions, and conflicts. This article discusses the noble qualities, originality, and artistic skill embodied in the image of the king and the scholar.